2019
DOI: 10.1001/jamasurg.2018.4359
|View full text |Cite
|
Sign up to set email alerts
|

Association of Timing of Colostomy Reversal With Outcomes Following Hartmann Procedure for Diverticulitis

Abstract: IMPORTANCE The Hartmann procedure (end colostomy) remains a common operation for diverticulitis requiring surgery. However, the timing of subsequent colostomy reversal remains widely varied, and the optimal timing remains unknown. OBJECTIVE To investigate the association of the timing of colostomy reversal with operative outcomes. DESIGN, SETTING, AND PARTICIPANTS This retrospective analysis of the Healthcare Cost and Utilization Project State Inpatient Databases for California, Florida and Maryland included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…While 2 studies 3 , 27 comparing HP with PAPD characterized rates of ostomy reversal, few studies have directly compared rates of unplanned readmissions, to our knowledge. Despite a decreased rate of comorbidities and younger age among patients undergoing PAPD, we found that these patients had significantly more frequent readmissions on raw and adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…While 2 studies 3 , 27 comparing HP with PAPD characterized rates of ostomy reversal, few studies have directly compared rates of unplanned readmissions, to our knowledge. Despite a decreased rate of comorbidities and younger age among patients undergoing PAPD, we found that these patients had significantly more frequent readmissions on raw and adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of the four trials comparing primary anastomosis with Hartmann’s procedures, patients who had a primary anastomosis were more likely to not have a stoma at 12 months after surgery (risk ratio 1.34, 1.16 to 1.54) compared with those who had a Hartmann’s procedure 104105. Less than a third of patients undergo colostomy reversal within one year of a Hartmann’s procedure, and having a colostomy is a substantial detriment to quality of life 106. Take down surgery to reverse the stoma after primary anastomosis with ileostomy had a reduced risk (risk ratio 0.23, 0.07 to 0.70) of a major postoperative complication compared with take down surgery for a Hartmann’s procedure.…”
Section: Treatmentmentioning
confidence: 99%
“…HP was first developed with the intent of treating rectosigmoid carcinoma by Henry Hartmann and involves rectosigmoid colon resection with the creation of a colostomy. It has a variety of indications, including complicated diverticulitis and less commonly volvulus, ischemia, and perforation [ 9 ]. Studies report a significant reduction in quality of life and gradual social isolation in HP patients [ 3 , 7 ].…”
Section: Reviewmentioning
confidence: 99%